Formation of compositional gradient in AlSiC FGMs fabricated under huge centrifugal forces using solid-particle and mixed-powder methods - Jamian, Saifulnizan; Watanabe, Yoshimi; Satob, Hisashi (Elsevier, 2019)
Formations of graded distribution of SiC ceramic particles within the hollow cylindrical shaped Al/SiC functionally graded materials (FGMs) fabricated by centrifugal solid-particle method (CSPM) and centrifugal mixedpowder method (CMPM) under huge centrifugal force are experimentally and theoretically investigated. The movement of SiC ceramic particles in viscous liquid under centrifugal force is explained based on Stoke's law. The effect of compositional gradient of particles on viscosity is taken into account. Also, the effect of temperature distribution on viscosity and density are considered. A computer code to simulate the formation of compositional gradient in the Al/SiC FGMs fabricated by CSPM and CMPM is developed. From the results, it is found that the volume fraction of SiC ceramic particles can be graded from the inner to the outer surface of hollow cylindrical shaped Al/SiC FGMs by CSPM. Meanwhile by CMPM, the SiC ceramic particles can be dispersed on the outer surface of hollow cylindrical shaped Al/SiC FGMs. The graded distribution in Al/SiC FGMs under huge centrifugal force is found to be significantly affected by the mold temperature but less affected by the temperature of molten Al and casting atmosphere.